Influence of Cooperative Learning Model of Bamboo Dancing to Students Learning Outcomes in Social Sciences in Elementary School - Sri Rohartati (International Journal of Science and Applied Science: Conference Series, 2019)
This research is entitled, The Influence of Cooperative Learning Models Type Bamboo Dancing Against Learning Outcomes of Students in Social Sciences Subjects in Primary Schools. This study aims to describe the implementation and influence of the cooperative model type bamboo dancing on improving student learning outcomes in social science subjects. The research problem formulation was formulated as "Is there any influence of cooperative learning model type bamboo dancing on student learning outcomes on social science subjects in elementary school?" The research method used was an experiment with the nature of quantitative research. The research design used is Quasi Experimental Design. The population of this study were students of the Public elementary School Mandalawangi district Cipatat West Bandung District. The research instrument uses observation sheets and test questions. The results of the test research data show that there is an increase in learning outcomes of students in social studies learning in elementary schools with the use of a cooperative type type bamboo dancing, can be seen from the results of the t-test on the sig (2-tailed) section showing differences in learning outcomes of students in post- the test obtained 0,000 this shows 0,000 <0,05, then H0 is rejected means that there is a significant difference in the learning outcomes of students between the experimental class and the control class there are differences after treatment. This difference suggests that the experimental class is superior and better the results can be seen through the average social studies learning outcomes of students in the experimental class using bamboo dancing models. Based on the proof of the hypothesis that reads "there is a significant influence on cooperative learning models of bamboo dancing type on the learning outcomes of students on social science subjects in elementary schools", the H1 hypothesis is accepted.